Effects of video conferencing affordances on enjoyment and video conferencing fatigue: a motivational technology approach - Yang, Yujia (Nanyang Technological University, 2024)
Due to the overwhelming use of video conferencing (VC), students are increasingly participating in online meetings through this platform. However, research shows that frequent use of VC often leads to fatigue (Li et al., 2022). With VC being widely used and accepted, it continues to serve as a tool for formal meetings. However, previous research has focused on VC use in a general way. Therefore, it is particularly necessary to explore how students can mitigate VC fatigue in group meetings for educational purposes. The current project aims to explore VC affordances’ role in improving VC experiences and mitigating fatigue. Unlike past efforts to directly eliminate factors causing VC fatigue, in real-world meetings, some factors cannot be avoided. Therefore, this study, based on the adjusted Motivational Technology Model (Jung & Sundar, 2022), focuses on a mechanism that may help alleviate VC fatigue: enhancing positive experiences to prevent or mitigate fatigue in VC meetings. This study focuses on graduate students as they are more likely to use VC for group meetings rather than lectures (Chang et al., 2021). 35 graduate students were invited and data was gathered through six focus groups. The results indicate that it is indeed possible to alleviate VC fatigue by enhancing enjoyment. Additionally, the study identified the conflicts in enjoyment and VC fatigue at both the individual and member levels. Furthermore, the research also examined the impact of collaborative project attributes on VC fatigue. This study provides useful tips for improving VC use and adds a fresh perspective on how enjoyment influences the process.